THE WAYS OF IMPROVEMENT OF PROFESSIONAL PSYCHOLOGICAL TRAINING OF UKRAINIAN NATIONAL POLICE OFFICERS - Barko, Vadim Ivanivich; Ostapovich, Vladimir Petrovich; Barko, Vadim Vadimovich (PSYCHOLOGICAL JOURNAL, 2018)
The article is dedicated to discussion of some questions connected with improvement of professional psychological training of Ukrainian National police officers. The authors analyze Ukrainian and foreign experience of arrangement and realization of psychological training of police officers with the purpose of formation of high level of motivation, ability to resist to stresses, conflicts and other factors of risk, development of important professional qualities. The authors also suggest to supplement the present system of official police officer’s training with new direction − specific professional psychological training. The result of this training is confined in forming of special state of personality – psychological readiness for professional activity. Psychological readiness is complex formation that consists of several components: cognitive (a system of knowledge, necessary for successful professional activity); conative (a system of motives for stimulation of professional activity); operational (system of psychological skills) and personal (system of professionally important personal qualities). It is shown that professional psychological training is long process, that begins from elementary stage of professional training and continues during all professional activity of police officer. Professional psychological training implemented with the help of different educational methods such as role plays, psychodrama, case studies, brainstorming etc. The training foresees participating of practical psychologists and conducting of police service in extremal conditions. An important task of training process is to provide police officers with special training complexes with the purpose of development of required professional, behavioral and communicative skills and readiness to act in different police service situations. The authors underline that investigation of international experience and methods of police professional psychological training is an essential component of this work. They strongly recommend in the article to create Complex program of arrangement and realization of professional psychological training of police officers of National police of Ukraine. The program might be established by appropriate order of Ministry of internal affairs of Ukraine. Key words: National police of Ukraine, professional psychological training, psychological readiness, motivation, stress.